Preparation method and application of methanol-resistant PdCu alloy cathode material

By preparing methanol-resistant PdCu alloy cathode material with a bi-continuous porous structure, the problems of weak methanol toxicity resistance and insufficient oxygen reduction reaction activity in direct methanol fuel cells are solved, and higher methanol resistance and oxygen reduction catalytic activity are achieved, improving the performance and stability of the battery.

CN119812364APending Publication Date: 2025-04-11TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510007438.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In direct methanol fuel cells, traditional Pt metal catalysts have weak methanol toxicity resistance and insufficient oxygen reduction reaction activity, resulting in unstable battery performance.

Method used

By displacing, annealing and dealloying Pd and Cu, a methanol-resistant PdCu alloy cathode material with a bi-continuous porous structure was prepared, and the Pd/Cu atomic ratio was controlled to improve the methanol resistance and oxygen reduction catalytic activity of the material.

Benefits of technology

The methanol resistance and oxygen reduction catalytic activity of the cathode material of methanol-resistant PdCu alloys has been improved, and the electrochemical performance and stability of direct methanol fuel cells have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005227340100000132
    Figure BDA0005227340100000132
  • Figure BDA0005227340100000141
    Figure BDA0005227340100000141
  • Figure BDA0005227340100000151
    Figure BDA0005227340100000151
Patent Text Reader

Abstract

The invention provides a preparation method of a methanol-resistant PdCu alloy cathode material, which comprises the following steps: carrying out replacement on a copper foil and a palladium replacement solution to obtain a Pd-Cu alloy precursor, controlling the atomic ratio of Pd / Cu in the Pd-Cu alloy precursor to be less than 1 / 3, then annealing at 300-500 DEG C for more than 24 hours to obtain a PdCu alloy film precursor, and finally preparing the methanol-resistant PdCu alloy cathode material. The PdCu alloy film precursor is subjected to dealloying through an acid system, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material is controlled to be larger than 5, and the methanol-resistant PdCu alloy cathode material of a bicontinuous porous structure is obtained. According to the methanol-resistant PdCu alloy cathode material and the preparation method thereof, the problems that a traditional Pt group metal catalyst is weak in methanol poison resistance and insufficient in ORR activity are solved, and the methanol-resistant PdCu alloy cathode material with high methanol resistance and high ORR catalytic capacity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of direct methanol fuel cells, and in particular to a preparation method and application of a methanol-resistant PdCu alloy cathode material. Background Art

[0002] In recent years, with the rapid increase in the global population and the continuous development of global trade services, the consumption of traditional fossil energy and environmental problems have made the demand for renewable energy and clean energy increasingly urgent. It has become a global consensus to explore alternative energy to reduce dependence on fossil energy and reduce the adverse effects of pollution emissions on the environment. In this context, fuel cell technology has attracted widespread attention due to its advantages such as renewable fuel, low noise operation, and pollution-free power generation process. Fuel cells are electrochemical energy conversion devices that directly convert chemical energy in substances into electrical energy. Compared with the traditional fossil fuel combustion process, its energy conversion process is not limited by the Carnot cycle and does not produce harmful nitrogen compounds or sulfides. Therefore, fuel cells are regarded as an important part of future clean energy.

[0003] Among the many types of fuel cells, direct methanol fuel cell (DMFC) has attracted much attention. DMFC uses methanol as a direct fuel to react with oxygen to directly generate electricity. Compared with hydrogen fuel cells, DMFC does not use hydrogen and therefore has a simple system design and operation process, and has a lower start-up temperature and higher volume energy density. Therefore, DMFC is regarded as an ideal choice for individual combat power and outdoor mobile power. However, although DMFC has many advantages in theory, its commercial application process still faces many challenges. During the operation of DMFC, methanol will penetrate from the anode to the cathode through the membrane. This penetration will not only lead to fuel waste, but also may cause the Pt group metal catalyst of the cathode to be poisoned, resulting in poor stability of the membrane electrode at high concentrations, thereby seriously reducing the overall performance of the battery. More importantly, the cathode is usually faced with oxygen reduction reaction and methanol oxidation reaction at the same time. Improving methanol resistance means that the material needs to be able to resist the toxicity of methanol, which often interferes with the oxygen reduction reaction. Therefore, how to improve the cathode oxygen reduction (Oxygen Reduction Reaction, ORR) activity and optimize the methanol poisoning resistance is a major difficulty in current research. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention proposes a method for preparing a methanol-resistant PdCu alloy cathode material. By replacing Pd and Cu, annealing and dealloying, a methanol-resistant PdCu alloy cathode material with a double continuous porous structure is obtained, which solves the problems of weak methanol poisoning resistance and insufficient ORR activity of traditional Pt group metal catalysts, and obtains a methanol-resistant PdCu alloy cathode material with high methanol resistance and high ORR catalytic ability.

[0005] The preparation method of the methanol-resistant PdCu alloy cathode material provided by the present invention is as follows:

[0006] S1: replacing the copper foil with the palladium replacement solution to obtain a Pd-Cu alloy precursor, and controlling the atomic ratio of Pd / Cu in the Pd-Cu alloy precursor to be less than 1 / 3;

[0007] S2: annealing at 300° C.-500° C. for more than 24 hours to obtain an annealed PdCu alloy thin film precursor;

[0008] S3: Dealloying the PdCu alloy film precursor through an acidic system to control the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material to be greater than 5.

[0009] As some preferred solutions, in step S1, the Pd / Cu atomic ratio in the Pd-Cu alloy thin film precursor is controlled to be 1 / 4-1 / 30.

[0010] As a further solution, in the step S1, the solute in the palladium replacement solution is selected from palladium salt, and the solvent is selected from acid solution.

[0011] As a further solution, the acid solution is selected from any one or more of nitric acid, hydrochloric acid and sulfuric acid.

[0012] As a further solution, in step S1, the Pd / Cu atomic ratio in the PdCu alloy thin film precursor can be regulated by adjusting the copper foil thickness, surface density, palladium replacement solution, replacement time, and replacement temperature.

[0013] As some reference schemes, the copper foil thickness can be selected from 100 nm to 10 μm, the palladium solution concentration can be selected from 0.01 mM to 10 mM, the replacement time can be 10 min to 24 h, and the replacement temperature can be 4° C. to 80° C.

[0014] As some preferred schemes for reference, the thickness of the copper foil can be selected from 300nm to 800nm, the concentration of the palladium solution can be selected from 0.5mM to 5mM, the replacement time can be 5h to 15h, and the replacement temperature can be 20°C to 60°C.

[0015] As a further solution, after the annealing in step S2 is completed, the atmosphere needs to continue to be introduced until it is cooled to room temperature.

[0016] As a further solution, the annealing atmosphere in step S2 is selected from hydrogen or a mixture of hydrogen and an inert gas.

[0017] As a further solution, in step S2, the annealing time is selected from 24h-50h, and the annealing temperature is selected from 350°C-450°C.

[0018] As some preferred solutions, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material in step S3 is selected from 5 / 1-25 / 1.

[0019] As a further solution, in step S3, the acidic system is selected from any one of an acid solution or an acidic inorganic salt solution that can react with Cu to form a soluble substance.

[0020] As a further solution, the dealloying method in step S3 is selected from any one of a free corrosion process and an electro-corrosion process.

[0021] As some preferred schemes, when dealloying is carried out through a free corrosion process, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material can be regulated by controlling the type, concentration, and free corrosion time of the acid solution or the acidic inorganic salt solution that can generate soluble substances with Cu in the acidic system.

[0022] As some preferred schemes for reference, when dealloying is carried out by a free corrosion process, the concentration of the acid solution or the acidic inorganic salt solution that can generate soluble substances with Cu is selected from 0.1M to 4M, and the corrosion time is selected from 0.5h to 24h.

[0023] As a further solution, the acid solution in step S3 may preferably be nitric acid, the concentration may preferably be 0.8M-2M, and the corrosion time may be selected from 3h-10h.

[0024] As a further solution, the electrocorrosion process uses the annealed PdCu alloy film precursor as the working electrode, uses nitric acid as the electrolyte, the nitric acid concentration is selected from 0.05M to 1M, and the applied voltage is 0.1V-1V (refer to the open circuit potential E OCV ), the corrosion is terminated when the corrosion current drops to microamperes.

[0025] As a further solution, the termination potential of the electrocorrosion process is selected from 0.8-0.5Vvs.E OCV .

[0026] As a further solution, the termination potential of the electrocorrosion process is selected from 0.70-0.5Vvs.E OCV .

[0027] As a further solution, the electrocorrosion process is a two-electrode system, and there is no limitation on the electrodes.

[0028] In the second aspect, the present scheme also provides a methanol-resistant PdCu alloy cathode material prepared by the above method, wherein the atomic ratio of Pd to Cu is greater than 5 and there is a bicontinuous porous structure, the pore size range of the bicontinuous porous structure is 4nm-13nm, and the ligament size range of the bicontinuous porous structure is 5nm-15nm.

[0029] As a further solution, in the methanol-resistant PdCu alloy cathode material, the Pd / Cu atomic ratio is selected from 5 / 1-25 / 1, the pore size range of the bicontinuous porous structure is 5nm-8nm, and the ligament size range is 6nm-8nm.

[0030] As a further solution, the methanol-resistant PdCu alloy cathode material has a specific surface area range of 70 m 2 / g-85m 2 / g.

[0031] As a further solution, the specific surface area range of the methanol-resistant PdCu alloy cathode material is preferably 74 m 2 / g-85m 2 / g.

[0032] Compared with the prior art, the present invention has at least the following beneficial effects:

[0033] By metal replacement, annealing and dealloying of Pd and Cu, the present invention prepares a methanol-resistant PdCu alloy cathode material with a bicontinuous porous structure. The bicontinuous porous structure constructed by Pd and Cu improves the ORR catalytic activity while optimizing the methanol resistance. At the same time, the unique pore distribution and ligaments of the bicontinuous porous structure improve the mass transfer efficiency and electronic conductivity of the methanol-resistant Pd-Cu alloy cathode material. In addition, the increase in specific surface area brought by the bicontinuous porous structure can also provide a higher active specific surface area, thereby optimizing the electrochemical performance of the methanol-resistant PdCu alloy cathode material. When the thin film electrode of the present invention is applied to a direct methanol fuel cell, the battery exhibits excellent stability and electrocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0035] Figure 1a, b, c, and d are TEM images of the methanol-resistant PdCu alloy cathode material prepared in Example 1, wherein the scale bar of a is 50 nm, the scale bar of b is 20 nm, the scale bar of c is 10 nm, and the scale bar of d is 2 nm;

[0036] Figure 2 In the figure, a is the cyclic voltammetry curve of Example 1, Example 7 and Comparative Example 1, b is the ECSA histogram of Example 1, Example 7 and Comparative Example 1, c is the oxygen reduction polarization curve experimental diagram of Example 1, Example 7 and Comparative Example 1, d is the oxygen reduction area activity and mass activity histogram of Example 1, Example 7 and Comparative Example 1;

[0037] Figure 3 The CO removal test diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are shown;

[0038] Figure 4 : The oxygen reduction polarization curves of Example 1 and Comparative Example 2 in methanol and perchloric acid electrolytes with concentrations of 0.005M, 0.01M, 0.05M, 0.1M, and 0.2M;

[0039] Figure 5 In the figure, a and b are respectively polarization curve test experimental diagrams of Example 1 and Comparative Example 2 at 5M, 7M, 9M and 11M methanol concentrations;

[0040] Figure 6 This is the XRD pattern of the methanol-resistant PdCu alloy cathode material prepared in Comparative Example 7;

[0041] Figure 7 a is the cyclic voltammetry curve of Example 1, Comparative Examples 10 and 11, b is the experimental diagram of oxygen reduction polarization curve of Example 1, Comparative Examples 10 and 11, and c is the histogram of oxygen reduction area activity and mass activity of Example 1, Comparative Examples 10 and 11;

[0042] Figure 8 In the figure, a is the XRD pattern before and after annealing in Example 1, and b is the XRD pattern of the methanol-resistant PdCu alloy cathode material prepared in Example 1;

[0043] Fig. 9 Figure a is a constant current discharge experimental diagram of the direct methanol fuel cell membrane electrode prepared in Example 1, and figure b is a cathode cyclic voltammetry curve comparison experimental diagram of the direct methanol fuel cell membrane electrode prepared in Example 1 before and after the constant current test. DETAILED DESCRIPTION

[0044] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.

[0045] In the first aspect, the preparation method of the methanol-resistant PdCu alloy cathode material provided by the present invention is as follows:

[0046] S1: replacing the copper foil with the palladium replacement solution to obtain a Pd-Cu alloy precursor, and controlling the atomic ratio of Pd / Cu in the Pd-Cu alloy precursor to be less than 1 / 3;

[0047] S2: annealing at 300° C.-500° C. for more than 24 hours to obtain an annealed PdCu alloy thin film precursor;

[0048] S3: Dealloying the PdCu alloy film precursor through an acidic system to control the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material to be greater than 5.

[0049] As one of the elements of the Pt group, Pd has an electronic configuration similar to that of Pt. At the same time, compared with Pt, the adsorption strength of Pd on methanol is usually lower. Therefore, it is difficult for methanol adsorbed on the surface of Pd to form a strong intermediate, thereby reducing unnecessary side reactions and poisoning. This unique property enables it to exhibit excellent tolerance when used as a cathode catalyst in DMFC. Although it has a high methanol tolerance, when Pd is used to catalyze ORR, Pd exhibits slightly weaker performance than Pt. Therefore, in the present invention, we combine Pd with Cu, and by controlling the ratio of Pd to Cu during replacement and corrosion, combined with the control of annealing time and temperature, we prepare a methanol-resistant PdCu alloy cathode material with a double continuous porous structure.

[0050] For methanol-resistant PdCu alloy cathode materials, the introduction of Cu helps to utilize copper's lower atomic radius and d-band filling degree to promote the contraction of the Pd lattice, and move the d-band center of Pd downward, weakening the excessive oxygen adsorption energy on the Pd surface, thereby enhancing the catalytic ability of the methanol-resistant PdCu alloy cathode material for ORR; through replacement, annealing and dealloying, we can remove part of Cu to form a bicontinuous porous structure in which the ligaments and pores are three-dimensionally interconnected, the ligaments are three-dimensional continuums, and the pores are also three-dimensional continuum structures.

[0051] Secondly, this scheme first replaces Pd with Cu, then achieves full dispersion of Pd and Cu through annealing, and removes excess Cu through dealloying to construct a bicontinuous porous structure. By controlling the atomic ratio of Pd to Cu after replacement to be less than 1 / 3, we further ensure that we have enough Cu for removal in the dealloying step on the basis of ensuring sufficient diffusion of Cu in Pd, thereby forming a bicontinuous porous structure. When the atomic ratio of Pd to Cu after replacement is less than 1 / 40, it may not be possible to ensure that an ideal bicontinuous porous structure can be formed after the dealloying process. On the other hand, the atomic ratio of Pd to Cu after replacement is less than 1 / 3, which can also avoid the generation of PdCu3 intermetallic compounds that are difficult to remove by dealloying during the subsequent annealing process, further ensuring that the generated bicontinuous porous structure is stable and uniform, thereby improving the electrochemical performance of DMFC.

[0052] On the basis of controlling the atomic ratio of Pd / Cu to be less than 1 / 3, this scheme further realizes the preparation of PdCu alloy film precursor by annealing. By controlling the annealing time and temperature, Pd and Cu can be dispersed with each other. It is worth noting that although controlling the atomic ratio of Pd / Cu to be less than 1 / 3 helps to avoid the formation of PdCu3 intermetallic compounds, when the annealing temperature exceeds 500°C, PdCu3 intermetallic compounds that cannot be removed may also be generated. Therefore, it is necessary to further regulate the annealing temperature based on the control of the Pd / Cu range. First of all, being lower than 500°C does not mean that the lower the annealing temperature, the better. For example, when the temperature is lower than 300°C, it may not provide enough kinetic energy to achieve mutual diffusion of Pd and Cu. Secondly, even if the temperature conditions are met, when the annealing time is less than 24h, Pd and Cu with different diffusion rates may not be able to achieve sufficient mutual diffusion, resulting in uneven bicontinuous porous structure of the methanol-resistant PdCu alloy cathode material obtained by subsequent dealloying; therefore, it is necessary to further control the annealing time and temperature; on this basis, through dealloying, this scheme constructs a methanol-resistant PdCu alloy cathode material with a bicontinuous porous structure, and further controls the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material by dealloying. When the Pd / Cu atomic ratio is greater than 5, it helps to construct a uniform bicontinuous porous structure, while improving the ORR catalytic ability of the methanol-resistant PdCu alloy cathode material, optimizing its methanol resistance, and obtaining a methanol-resistant PdCu alloy cathode material with both excellent electrochemical properties and methanol resistance.

[0053] As some preferred schemes, controlling the Pd / Cu atomic ratio in the Pd-Cu alloy film precursor to be 1 / 4-1 / 30 in step S1 helps to further optimize the ratio between Pd and Cu and obtain a more uniformly dispersed PdCu alloy precursor, so as to facilitate the construction of a more uniform bicontinuous porous structure.

[0054] As a further solution, in the step S1, the solute in the palladium replacement solution is selected from palladium salt, and the solvent is selected from acid solution.

[0055] As a further solution, the palladium salt is selected from any one or more of palladium nitrate, palladium chloride, and sodium chloropalladate.

[0056] As a further solution, the acid solution is selected from any one or more of nitric acid, hydrochloric acid and sulfuric acid.

[0057] As a further solution, in step S1, the Pd / Cu atomic ratio in the PdCu alloy thin film precursor can be regulated by adjusting the copper foil thickness, palladium replacement solution, replacement time, and replacement temperature.

[0058] As some reference schemes, the copper foil thickness can be selected from 100 nm to 10 μm, the palladium solution concentration can be selected from 0.01 mM to 10 mM, the replacement time can be 10 min to 24 h, and the replacement temperature can be 4° C. to 80° C.

[0059] As some preferred schemes for reference, the thickness of the copper foil can be selected from 300nm to 800nm, the concentration of the palladium solution can be selected from 0.5mM to 5mM, the replacement time can be 5h to 15h, and the replacement temperature can be 20°C to 60°C.

[0060] As a further solution, the atmosphere needs to be continuously introduced after the annealing in step S2 is completed until it is cooled to room temperature, so as to prevent the PdCu alloy film precursor material that has been annealed but not cooled from being oxidized again when it comes into contact with air at high temperature.

[0061] As a further preferred embodiment, the annealing atmosphere in step S2 is selected from hydrogen or a mixture of hydrogen and an inert gas.

[0062] As some reference schemes, the inert gas is selected from any one of helium, neon, argon, krypton, xenon and radon.

[0063] As a further solution, the annealing time in step S2 is selected from 24h-50h, and the annealing temperature is selected from 350℃-450℃. The selection of this annealing time and temperature not only helps to ensure that Pd and Cu with different diffusion rates are fully diffused to form a uniform alloy, but also enables the CuO generated in the replacement reaction to be better reduced, thereby forming a more uniform bicontinuous porous structure, thereby improving the ORR catalytic performance of the methanol-resistant PdCu alloy cathode material.

[0064] As some preferred schemes, the Pd / Cu atomic ratio in the methanol-resistant Pd-Cu alloy cathode material in step S3 is selected from 5 / 1-25 / 1, which helps to construct a bicontinuous porous structure with more uniform distribution, more reasonable pore size and more stable ligaments.

[0065] As a further solution, in step S3, the acidic system is selected from any one of an acid solution or an acidic inorganic salt solution that can react with Cu to form a soluble substance.

[0066] As a further embodiment, the acid is selected from any one of hydrochloric acid, nitric acid and sulfuric acid.

[0067] As a further solution, the acidic inorganic salt is selected from any one of ammonium sulfate and ammonium chloride.

[0068] As a further solution, the dealloying method in step S3 is selected from any one of a free corrosion process and an electro-corrosion process.

[0069] As some preferred schemes, when dealloying is carried out through a free corrosion process, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material can be regulated by controlling the type, concentration, and free corrosion time of the acid solution or the acidic inorganic salt solution that can generate soluble substances with Cu in the acidic system.

[0070] As some preferred schemes for reference, when dealloying is carried out by a free corrosion process, the concentration of the acid solution or the acidic inorganic salt solution that can generate soluble substances with Cu is selected from 0.1M to 4M, and the corrosion time is selected from 0.5h to 24h.

[0071] As a further solution, the acid solution in step S3 may preferably be nitric acid, the concentration may preferably be 0.8M-2M, and the corrosion time may be selected from 3h-10h.

[0072] As a further solution, the electrocorrosion process uses the annealed PdCu alloy film precursor as the working electrode, uses nitric acid as the electrolyte, and uses the "current-time" program in the electrochemical workstation. This program can apply a constant potential to the PdCu film and detect and record the change of the corrosion current value of the PdCu film at this potential over time. By applying a constant potential, most of the elemental Cu in the PdCu alloy film is driven to further corrode and dissolve in the electrolyte. The nitric acid concentration of the electrolyte is selected from 0.05M to 1M, and the external constant voltage is 0.1V-1V (refer to the open circuit potential E OCV ). Since electrocorrosion intensifies with the increase of applied potential, in order to control the corrosion rate and protect the structural stability of the film electrode, the applied potential needs to be applied incrementally. The smaller the PdCu corrosion current collected by the electrochemical workstation during the electrocorrosion process, the more thorough the corrosion of the PdCu film at this potential. When the corrosion current drops to microampere units, the current corrosion process can be terminated and the next step of electrocorrosion can be carried out according to a certain potential increase.

[0073] As a further solution, the termination potential of the electrocorrosion process is selected from 0.8-0.5Vvs.E OCV .

[0074] As a further solution, the termination potential of the electrocorrosion process is selected from 0.7-0.5Vvs.E OCV .

[0075] As a further solution, the electro-corrosion process only includes a working electrode and a counter electrode. The counter electrode is not limited, and technicians can select the counter electrode according to their needs. For example, a carbon plate can be selected as the counter electrode.

[0076] As some preferred schemes for reference, in the electro-corrosion process, the concentration of nitric acid is selected from 0.1M-0.5M, and the applied voltage is 0.1V-0.6V (refer to open circuit potential).

[0077] As a further solution, in the electrocorrosion process, the potential increase may preferably be 50 mV.

[0078] In the second aspect, the present scheme also provides a methanol-resistant PdCu alloy cathode material prepared by the above method, wherein the atomic ratio of Pd to Cu is greater than 5 and there is a bicontinuous porous structure, the pore size range of the bicontinuous porous structure is 4nm-13nm, and the ligament size range of the bicontinuous porous structure is 5nm-15nm.

[0079] When the atomic ratio of Pd to Cu is greater than 5, on the one hand, it helps to construct a bicontinuous porous structure with a pore size range of 4nm-13nm and a ligament range of 5nm-15nm. The construction of the bicontinuous porous structure helps to improve the electronic conductivity by utilizing its continuous ligaments. Secondly, the three-dimensional through-holes of the bicontinuous porous structure can also effectively improve the mass transfer efficiency, thereby greatly improving the output power of DMFC. Thirdly, when the atomic ratio of Pd to Cu is greater than 5, the ability of Pd to resist methanol poisoning can be maximized, and on this basis, the ORR activity can be further optimized to improve the performance stability of DMFC.

[0080] As a further solution, in the methanol-resistant PdCu alloy cathode material, the Pd / Cu atomic ratio is selected from 5 / 1-25 / 1, which helps to form a bicontinuous porous structure with more uniform pore distribution, more reasonable pore size, and more stable ligaments, and the pore size range is 5nm-8nm, and the ligament size range is 6nm-8nm. When the Pd / Cu atomic ratio is selected from 5 / 1-25 / 1, the pore size range is 5nm-8nm, and the ligament range is 6nm-8nm, its uniformly distributed bicontinuous pores help to further optimize ionic conductivity and mass transfer efficiency. Furthermore, its uniform ligaments also help to fully disperse internal stress and extend battery life.

[0081] As a further solution, the Pd(111) interplanar spacing in the methanol-resistant Pd-Cu alloy cathode material is 0.195nm-0.215nm. Due to the introduction of Cu, the Pd lattice shrinks from the standard 0.225nm lattice of Pd(111) to 0.195nm-0.215nm. The shrinkage of Pd helps to reduce the excessive oxygen adsorption energy on the Pd surface and improve the oxygen reduction activity.

[0082] As a further solution, the Pd(111) interplanar spacing is selected from 0.2nm-0.21nm. The Pd(111) interplanar spacing of 0.2nm-0.21nm can further adjust the oxygen adsorption energy on the Pd surface and improve the battery performance.

[0083] As a further solution, the methanol-resistant Pd-Cu alloy cathode material has a specific surface area range of 70 m 2 / g-85m 2 / g. When the specific surface area range is 70m 2 / g-85m 2 / g, it helps to provide more active sites, thereby improving the ORR catalytic activity.

[0084] As a further solution, the specific surface area range of the methanol-resistant Pd-Cu alloy cathode material may preferably be 74 m 2 / g-85m 2 / g in order to provide more active sites.

[0085] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0086] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0087] Example 1

[0088] Preparation of Methanol-Resistant PdCu Alloy Cathode Material

[0089] S1: PdCl2 was dissolved in hydrochloric acid and diluted to 1 mM to obtain a palladium replacement solution. A copper foil with a thickness of about 500 nm was floated in the palladium replacement solution at 25°C for 10 hours to obtain a Pd-Cu precursor with a Pd / Cu atomic ratio of 1 / 10.

[0090] S2: Fix the Pd-Cu precursor with carbon paper and anneal it at 400°C for 28h in an argon-hydrogen atmosphere. After the annealing process is completed, continue to introduce argon-hydrogen gas until it drops to room temperature to obtain an annealed PdCu alloy film precursor.

[0091] S3: Using 0.1M HNO3 solution as electrolyte, PdCu alloy film as working electrode, carbon plate as counter electrode and reference electrode, the open circuit voltage E of the corrosion system was measured. OCV The “current-time” program in the electrochemical workstation was used to perform constant potential corrosion on the PdCu film. The applied voltage was (E OCV +0.1)V, stop when the corrosion current drops to microamperes, and increase the applied voltage to (E OCV +0.15)V to carry out the next potential corrosion, repeat the above electrocorrosion process, the potential increase is 50mV, the termination potential is (E OCV +0.65) V. After the corrosion is completed, a methanol-resistant Pd-Cu alloy cathode material is obtained, and the Pd / Cu atomic ratio is 5 / 1. The prepared methanol-resistant Pd-Cu alloy cathode material is floated in deionized water for later use.

[0092] Preparation of membrane electrode for direct methanol fuel cell

[0093] First, the methanol-resistant Pd-Cu alloy cathode material was attached to the surface of polytetrafluoroethylene (PTFE) film and the moisture was wiped off. Secondly, the methanol-resistant Pd-Cu alloy cathode material was transferred to the surface of Nafion 115 proton exchange membrane by hot pressing. The hot pressing temperature was 120 °C and the pressure was 50 kg / cm 2 , the hot pressing time is 2min.

[0094] Finally, the Pt loading of 2 mg cm -2 Commercial PtRu / C gas diffusion electrode, Nafion115 proton exchange membrane, 20% PTFE treated cathode gas diffusion layer (200 μm carbon paper sprayed with 2 mg / cm 2 The present invention relates to a direct methanol fuel cell membrane electrode (DMFC) combination, wherein one side of the Nafion 115 proton exchange membrane having the methanol-resistant Pd-Cu alloy cathode material is in contact with a cathode gas diffusion layer treated with 20% PTFE, followed by hot pressing at 130° C. for 90 seconds, turning over, and hot pressing again for 90 seconds.

[0095] Example 2

[0096] The preparation method and steps are the same as those in Example 1, except that the concentration of the palladium replacement solution is selected from 0.5 mM, the replacement time is selected from 5 h, and the replacement temperature is selected from 20° C. The Pd / Cu atomic ratio in the obtained Pd-Cu alloy thin film precursor is 1 / 30.

[0097] Example 3

[0098] The preparation method and steps are the same as those in Example 1, except that the concentration of the palladium replacement solution is selected from 5 mM, the replacement time is selected from 15 h, and the replacement temperature is selected from 60° C. The Pd / Cu atomic ratio in the obtained Pd-Cu alloy thin film precursor is 1 / 4.

[0099] Example 4

[0100] The preparation method and steps are the same as those in Example 1, except that the annealing time is selected from 24 h and the annealing temperature is selected from 350° C.

[0101] Example 5

[0102] The preparation method and steps are the same as those in Example 1, except that the annealing time is selected from 50 h and the annealing temperature is selected from 350° C.

[0103] Example 6

[0104] The preparation method and steps are the same as those in Example 1, except that the annealing time is selected from 50 h and the annealing temperature is selected from 450° C.

[0105] Example 7

[0106] The preparation method and steps are the same as those in Example 1, except that the dealloying is performed by a free corrosion process. The steps of the free corrosion process are as follows: the PdCu alloy film precursor is placed in a 1M HNO3 solution for corrosion for 6 hours, and then washed with deionized water to obtain a methanol-resistant PdCu alloy cathode material.

[0107] Example 8

[0108] The preparation method and steps are the same as those in Example 1, except that during the electrocorrosion process, the HNO3 concentration is 0.05M.

[0109] Example 9

[0110] The preparation method and steps are the same as those in Example 1, except that during the electrocorrosion process, the HNO3 concentration is 1 M and the termination potential is 0.8 V vs. E OCV .

[0111] Comparative Example 1

[0112] A 10% Pd / C commercial catalyst was used as the cathode catalyst, and the manufacturer was Alfa Aesar (China) Chemical Co., Ltd.

[0113] Comparative Example 2

[0114] A 20% Pt / C commercial catalyst was used as the cathode catalyst, and the manufacturer was Johnson Matthey (Shanghai) Chemical Co., Ltd.

[0115] Comparative Example 3

[0116] The preparation method and steps are the same as those in Example 1, except that annealing is not performed during the preparation of the methanol-resistant PdCu alloy cathode material.

[0117] Comparative Example 4

[0118] The preparation method and steps are the same as those of Example 1, except that dealloying is not performed during the preparation of the methanol-resistant PdCu alloy cathode material.

[0119] Comparative Example 5

[0120] The preparation method and steps are the same as those in Example 1, except that the concentration of the palladium replacement solution is selected from 11 mM, the replacement time is selected from 25 h, the replacement temperature is selected from 85° C., and the Pd / Cu atomic ratio in the obtained Pd-Cu alloy film precursor is 1 / 2.

[0121] Comparative Example 6

[0122] The preparation method and steps are the same as those of Example 1, except that the concentration of the palladium replacement solution is selected from 0.005 mM, the replacement time is selected from 0.084 h, the replacement temperature is selected from 3° C., and the Pd / Cu atomic ratio in the obtained Pd-Cu alloy film precursor is 1 / 60.

[0123] Comparative Example 7

[0124] The preparation method and steps are the same as those in Example 1, except that the annealing time is selected from 28 h and the annealing temperature is selected from 600° C.

[0125] Comparative Example 8

[0126] The preparation method and steps are the same as those in Example 1, except that the annealing time is selected from 10 h and the annealing temperature is selected from 400° C.

[0127] Comparative Example 9

[0128] The preparation method and steps are the same as those in Example 1, except that the corrosion is carried out by using a 0.01 M acetic acid solution for 4 hours.

[0129] Comparative Example 10

[0130] The preparation method and steps are the same as those in Example 1, except that the electrochemical corrosion termination potential is 0.4V.

[0131] Comparative Example 11

[0132] The preparation method and steps are the same as those in Example 1, except that the electrochemical corrosion termination potential is 0.1V.

[0133] Test method:

[0134] Electrochemical specific surface area (ECSA): The test was conducted using an electrochemical workstation with a three-electrode system. The working electrode was a glassy carbon electrode with a PdCu alloy film attached, the counter electrode was a platinum electrode, and the reference electrode was a saturated calomel electrode (SCE). Cyclic voltammetry (CV) was performed in a nitrogen-saturated 0.1M perchloric acid solution at a scan rate of 50mV / s in the potential range of -0.25-1.15V (vs.SCE). The Pd reduction peak area in the CV curve was integrated to obtain the amount of electricity (Q Pd-O ), through the formula Q Pd-O / (420μC / cm 2 ) to obtain the electrochemical active area of ​​Pd, and the electrochemical specific surface area of ​​Pd can be obtained by dividing the electrochemical active area by the Pd loading.

[0135] Oxygen reduction catalytic activity: The test was conducted using an electrochemical workstation with a three-electrode system. The working electrode was a rotating disk electrode with a PdCu alloy film attached, the counter electrode was a platinum electrode, and the reference electrode was a reversible hydrogen electrode (RHE). In an oxygen-saturated 0.1M perchloric acid or a perchloric acid + methanol mixed solution, the electrode speed was 1600rpm, and the linear sweep voltammetry (LSV) test was performed at a scan rate of 10mV / s. The potential range was 0.2-1.1Vvs.RHE. Under this test condition, the limiting current density of the oxygen reduction reaction was 6mA / cm 2 , so the current density is selected as 3mA / cm 2 The potential at is the half-wave potential. The catalytic activity is generally expressed by the KL equation (i, measured current; i k , kinetic current; i L , limiting current) to calculate the kinetic current i at 0.9Vvs.RHE k ,i k Normalized to the electrochemical active area to obtain the area activity, i.e., the intrinsic activity; i k The mass activity was normalized to the Pd loading to reflect the utilization of the precious metal.

[0136] Anti-CO poisoning ability: The test was conducted using an electrochemical workstation with a three-electrode system. The working electrode was a glassy carbon electrode with a PdCu alloy film attached, the counter electrode was a platinum electrode, and the reference electrode was a saturated calomel electrode (SCE). The working electrode was placed in 0.5M H2SO4 saturated with CO, and a potential of -0.15V was applied for constant potential CO adsorption. After 10 minutes, N2 was introduced into the electrolyte solution to remove CO from the solution while maintaining the applied potential unchanged. After 30 minutes of ventilation, a CV curve test was conducted with a starting potential of -0.24V, a potential range of -0.24-0.9V, and a forward scan at a scan rate of 20mV / s. The catalyst's anti-CO poisoning ability was evaluated by comparing the onset potential of the CO oxidation peak on the CV curve.

[0137] DMFC membrane electrode performance test: completed by a fuel cell test device (Scribner 850e), the anode is delivered with methanol solution by a peristaltic pump, and the cathode is passed with 100% humidified oxygen. The flow rate of the anode methanol solution is 2mL / min, the cathode oxygen flow rate is 300mL / min, and the operating temperature is 80°C. The IV and IP polarization curves are obtained by testing the change of the fuel cell voltage under different discharge currents, and the operation time of each current is 1min. The membrane electrode performance stability test process is to keep the membrane electrode constant at 100mA / cm 2 After discharging for 10 hours, the smaller the voltage drop of the membrane electrode in the stability test, the better the stability of the membrane electrode.

[0138] The test results of Examples 1-9 and Comparative Examples 1-11 are shown in Table 2 and Table 3.

[0139] Table 1

[0140]

[0141]

[0142]

[0143] Table 2

[0144]

[0145]

[0146] It can be observed from Examples 1-9 and Comparative Examples 1-11 that, compared with Comparative Examples 1-11, Example 1-9 as a whole exhibits a more uniform morphology, higher ORR catalytic activity, stronger resistance to methanol poisoning, and better cycle stability.

[0147] Table 3

[0148]

[0149] It can be seen from Example 1, Example 7 and Comparative Example 1 that when the methanol-resistant PdCu alloy cathode material prepared by this scheme is used as a catalyst (Example 1), the unique bicontinuous porous structure ( Figure 1 ) greatly increases the surface area of ​​the methanol-resistant Pd-Cu alloy cathode material, thereby improving the utilization rate of the Pd active sites. The ECSA of Example 7 and Comparative Example 1 are significantly smaller than that of Example 1 ( Figure 2 b), indicating that the utilization rate of active sites in Example 7 and Comparative Example 1 is low, and therefore, it also exhibits low oxygen reduction area activity and mass activity. At the same time, when 10% Pd / C (Comparative Example 1) and 20% Pt / C (Comparative Example 2) commercial catalysts are used as oxygen reduction catalysts, Figure 3 As can be seen from Table 3, the onset potential and peak potential of the CO oxidation peak of Example 1 are 0.785V and 0.865V, respectively. Compared with Comparative Example 1 (0.902V / 0.978V), the potentials are significantly positively shifted and slightly smaller than Comparative Example 2 (0.798V / 0.880V), which indicates that the methanol-resistant PdCu alloy cathode material prepared in Example 1 has higher CO tolerance than traditional commercial Pd / C and is comparable to commercial Pt / C. Next, the methanol tolerance of Example 1 and Comparative Example 2 is compared. Figure 4 As shown, it can be seen that Example 1 does not have a significant methanol oxidation peak or a significant shift in the ORR curve, showing excellent resistance to methanol poisoning. At the same time, in the membrane electrode test, as the methanol concentration gradually increases, the peak power density reduction shown by Comparative Example 2 is also much higher than that of Example 1 ( Figure 5 ), in comparison, Example 1 exhibits better performance as a whole, indicating that the methanol-resistant Pd-Cu alloy cathode material proposed in this scheme has strong resistance to methanol poisoning and catalytic ORR activity. When the methanol-resistant PdCu alloy cathode material is used as a catalyst, the direct methanol fuel cell membrane electrode prepared in Example 1 exhibits good methanol resistance and operation stability.

[0150] As can be seen from Table 2, in the process of preparing the methanol-resistant PdCu alloy cathode material, we first prepare the Pd-Cu alloy precursor by substitution reaction, then prepare the PdCu alloy film precursor by annealing, and finally remove part of the Cu element by dealloying to obtain a methanol-resistant PdCu alloy cathode material with a double continuous porous structure. It can be observed from Example 1 and Comparative Examples 3-4 that, on the one hand, the combination of substitution reaction, annealing and dealloying is very important for this scheme. No matter which step is lacking, the methanol-resistant PdCu alloy cathode material with a double continuous porous structure cannot be obtained. On the other hand, in the process of preparing the methanol-resistant PdCu alloy cathode material, it is also necessary to control its preparation steps. First, the uniform deposition of Pd on the copper foil is achieved by substitution reaction, and then the uniform diffusion of Pd and Cu is achieved by annealing. Finally, part of Cu is removed by dealloying. It is worth noting that in order to improve the methanol resistance of the methanol-resistant PdCu alloy cathode material while improving its ORR catalytic activity, it is also necessary to further control the parameters in its preparation process.

[0151] For the methanol-resistant Pd-Cu alloy cathode material, its unique bicontinuous porous structure greatly improves its ORR activity. Therefore, in the process of preparing the methanol-resistant PdCu alloy cathode material, we must first control the Pd / Cu atomic ratio in the Pd-Cu alloy precursor obtained in the replacement reaction to be less than 1 / 3. It can be observed from Example 1 and Comparative Examples 5 and 6 that when the Pd / Cu atomic ratio in the Pd-Cu alloy precursor is 1 / 2 (Comparative Example 5) or 1 / 60 (Comparative Example 6), it may lead to the inability to remove enough Cu in the subsequent dealloying process (such as Comparative Example 5) or the Pd content is too low to form a continuous ligament (such as Comparative Example 6) to form a methanol-resistant PdCu alloy cathode material with a bicontinuous porous structure. At the same time, when the Pd content is too large, it may also generate PdCu3 intermetallic compounds that cannot be removed during the annealing process, resulting in the bicontinuous porous pore size generated in the methanol-resistant PdCu alloy cathode material being affected, thereby affecting the specific surface area, and further resulting in the inhibition of ORR catalytic activity (Comparative Example 5).

[0152] From Example 1 and Comparative Examples 7-8, it can be observed that, on the basis of controlling the Pd / Cu atomic ratio in the PdCu alloy precursor to be between 1 / 3 and 1 / 40, the annealing conditions need to be controlled. When the annealing temperature is 600°C, Comparative Example 7 obtains a nanoporous structure PdCu3 intermetallic compound. This is because, although we control the Pd / Cu atomic ratio in the Pd-Cu alloy precursor to be within a suitable range, when the annealing temperature is 600°C, Pd and Cu generate an indelible PdCu3 intermetallic compound ( Figure 6), resulting in a large amount of Cu element residue, inhibiting the catalytic activity of Pd. When the annealing time is 10h (Comparative Example 8), although a bicontinuous pore structure is generated, since Pd and Cu have completely different diffusion rates, 10h of time cannot achieve sufficient mutual diffusion. Therefore, the pore size and ligament size range of Comparative Example 8 span a large range, resulting in a decrease in the specific surface area of ​​Pd and a decrease in the ORR catalytic activity. Therefore, according to Example 1, Comparative Examples 7-8, we further control the annealing temperature in the range of 300℃-500℃, and the annealing time is more than 24h.

[0153] In the methanol-resistant PdCu alloy cathode material, the introduction of Cu helps to weaken the excessive oxygen adsorption energy on the Pd surface and enhance the ORR catalytic ability, while Pd can provide the methanol-resistant Pd-Cu alloy cathode material with stronger methanol resistance. Example 1 and Comparative Examples 9-11 further discuss the effect of the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material on its performance. On the basis of satisfying the replacement and annealing conditions, it can be observed from Comparative Examples 9-11 that no matter what dealloying method is used, when the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material is less than 5, Comparative Examples 9-11 all show catalytic activity far inferior to that of Example 1. More importantly, it can be observed from the cyclic voltammetry curves of Example 1, Comparative Examples 10 and 11 that ( Figure 7 a), when the Pd / Cu atomic ratio is less than 5, the oxidation peak of Cu can be clearly observed near 0.63V in the CV curve, and the PdO reduction peak in the negative scan process is also larger due to the presence of Cu. As Cu decreases, its oxidation peak gradually weakens, and the reduction peak gradually narrows to the peak shape of PdO alone, and the half-wave potential also increases accordingly, and the ORR activity gradually increases ( Figure 7 b). Therefore, it is necessary to control the Pd / Cu atomic ratio to ≥5, so as to give full play to the compounding effect between Pd and Cu, and improve the electrochemical performance of the methanol-resistant PdCu alloy cathode material while improving its structural stability.

[0154] By adjusting the Pd / Cu atomic ratio in the PdCu alloy precursor, it is helpful to further optimize the morphology of the methanol-resistant Pd-Cu alloy cathode material and obtain a methanol-resistant Pd-Cu alloy cathode material with a uniform bicontinuous porous structure. It can be observed from Examples 1-3 that compared with Example 2 in which the Pd / Cu atomic ratio in the PdCu alloy precursor is 1 / 30 and Example 3 in which the Pd / Cu atomic ratio is 1 / 4, Example 1 exhibits a more uniform bicontinuous porous structure ( Figure 1), which may be because, when the ratio range in the PdCu alloy precursor is 1 / 4-1 / 30, it helps to provide more sufficient Cu for the subsequent construction of the bicontinuous porous structure. At the same time, satisfying the range of 1 / 4-1 / 30 can also obtain a more uniformly dispersed PdCu alloy precursor, which can achieve better dispersion in the subsequent annealing process, thereby constructing a more uniform bicontinuous porous structure.

[0155] Examples 1, 4-6 further discuss the effect of annealing conditions on the performance of methanol-resistant Pd-Cu alloy cathode materials. It can be observed from Examples 1, 4-6 that, compared with Example 4 with an annealing time of 24 h and Examples 5-6 with an annealing time of 50 h, when the annealing time reaches 28 h and the annealing temperature is 400 ° C (Example 1), the methanol-resistant PdCu alloy cathode material exhibits the best mass activity and redox area activity; this may be because the annealing step can not only achieve the mutual diffusion of Pd and Cu, but also achieve the reduction of copper oxide generated in the replacement reaction, Figure 8 It can be seen from a that after annealing, due to the reduction of CuO and the uniform diffusion of the two metals, the diffraction peak of CuO disappears, and several diffraction peaks are located between the standard peaks of Pd and Cu ( Figure 8 b), indicating that the annealing operation achieves the reduction of CuO and the uniform diffusion of the two metals. From Examples 1, 4-6, it can be seen that when the annealing time is selected from 28h-50h and the annealing temperature is selected from 350℃-450℃, it is helpful to obtain a methanol-resistant PdCu alloy cathode material with better ORR catalytic efficiency and methanol resistance.

[0156] Examples 1, 7-9 demonstrate the effects of the corrosion process and the Pd / Cu atomic ratio on the performance of the methanol-resistant PdCu alloy cathode material. It can be observed from Examples 1, 7-8 that although both the free corrosion process and the electro-corrosion process can control the Pd / Cu atomic ratio to be greater than 5 / 1, the electro-corrosion process can more accurately control the corrosion rate and uniformity compared to the free corrosion process. Therefore, the ECSA of Examples 1 and 8 is slightly greater than that of Example 7. In addition, by controlling the atomic ratio of Pd to Cu, we constructed a unique bicontinuous porous structure, which not only improves the ORR catalytic activity of the methanol-resistant PdCu alloy cathode material, but also ensures its tolerance to methanol. By adjusting the atomic ratio of Pd to Cu, we can observe that Example 1 exhibits higher ECSA and half-wave potential than Example 9. This may be because Example 1 has a larger specific surface area and a more uniform bicontinuous porous structure than Example 9, thereby improving the ORR catalytic activity. At the same time, as the methanol concentration gradually increases, Example 1 exhibits better methanol resistance than Example 9. This may be because compared with Example 9, the ligaments in the bicontinuous porous structure of Pd and Cu in Example 1 are more stable, which can effectively resist the poisoning of methanol to the methanol-resistant Pd-Cu alloy cathode material, thereby improving the stability under high methanol concentration. When used to prepare a direct methanol fuel cell membrane electrode, it also exhibits better cycle stability (the voltage decay rate of Example 1 is only 7.3%, as shown in Figure 2). Fig. 9 ), therefore, according to Examples 1, 7-9, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material can be preferably selected from 5 / 1-25 / 1.

[0157] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A method for preparing a methanol-resistant PdCu alloy cathode material, characterized in that: The steps include: S1: replacing the copper foil with the palladium replacement solution to obtain a Pd-Cu alloy precursor, and controlling the atomic ratio of Pd / Cu in the Pd-Cu alloy precursor to be less than 1 / 3; S2: annealing at 300° C.-500° C. for more than 24 hours to obtain an annealed PdCu alloy thin film precursor; S3: Dealloying the PdCu alloy film precursor through an acidic system to control the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material to be greater than 5.

2. The method for preparing the methanol-resistant PdCu alloy cathode material according to claim 1, characterized in that: In the step S1, the Pd / Cu atomic ratio in the Pd-Cu alloy thin film precursor is controlled to be 1 / 4-1 / 30.

3. The method for preparing the methanol-resistant PdCu alloy cathode material according to claim 1, characterized in that: In the step S1, the solute in the palladium replacement solution is selected from palladium salt, and the solvent is selected from acid solution; Preferably, the acid solution is selected from any one or more of nitric acid, hydrochloric acid and sulfuric acid.

4. The method for preparing the methanol-resistant PdCu alloy cathode material according to claim 1, characterized in that: In the step S1, the Pd / Cu atomic ratio in the PdCu alloy thin film precursor can be regulated by adjusting the copper foil thickness, the palladium replacement solution, the replacement time, and the replacement temperature; Preferably, the copper foil thickness can be selected from 100 nm to 10 μm, the palladium solution concentration can be selected from 0.01 to 10 mM, the replacement time can be 10 min to 24 h, and the replacement temperature can be 4° C. to 80° C.; Preferably, the thickness of the copper foil can be selected from 300 nm to 800 nm, the concentration of the palladium solution can be selected from 0.5 to 5 mM, the replacement time can be 5 h to 15 h, and the replacement temperature can be 20° C. to 60° C.

5. The method for preparing the methanol-resistant PdCu alloy cathode material according to claim 1, characterized in that: In step S2, after the annealing is completed, the atmosphere needs to be continuously introduced until the annealing is cooled to room temperature; Preferably, the annealing atmosphere is selected from hydrogen or a mixture of hydrogen and an inert gas; Preferably, in step S2, the annealing time is selected from 24h-50h, and the annealing temperature is selected from 350°C-450°C.

6. The method for preparing the methanol-resistant PdCu alloy cathode material according to claim 1, characterized in that: In the step S3, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material is selected from 5 / 1 to 25 / 1; Preferably, in step S3, the acidic system is selected from any one of an acid solution or an acidic inorganic salt solution that can react with Cu to form a soluble substance.

7. The method for preparing the methanol-resistant PdCu alloy cathode material according to claim 1, characterized in that: The dealloying method in step S3 is selected from any one of a free corrosion process and an electro-corrosion process; Preferably, when dealloying is performed by a free corrosion process, the Pd / Cu atomic ratio in the methanol-resistant PdCu alloy cathode material can be regulated by controlling the type, concentration, and free corrosion time of the acid solution or the acidic inorganic salt solution that can generate soluble substances with Cu in the acidic system; Preferably, when dealloying is performed by a free corrosion process, the concentration of the acid solution or the acidic inorganic salt solution that can generate soluble substances with Cu is selected from 0.1 to 4 M, and the corrosion time is selected from 0.5 h to 24 h; Preferably, the acid solution may be nitric acid, the concentration may be 0.8M to 2M, and the corrosion time may be 3h to 10h; Preferably, the electrocorrosion process uses the annealed PdCu alloy film precursor as an electrode, uses nitric acid as an electrolyte, the nitric acid concentration is selected from 0.05M to 1M, and the applied voltage is 0.1V-1V (refer to the open circuit potential E OCV ), the corrosion is terminated when the corrosion current is reduced to microamperes; Preferably, the termination potential of the electrocorrosion process is selected from 0.8-0.5Vvs.E OCV ; Preferably, the termination potential of the electrocorrosion process is selected from 0.7-0.5Vvs.E OCV .

8. A methanol-resistant PdCu alloy cathode material, characterized in that: Prepared by the method according to any one of claims 1 to claim 7.

9. The methanol-resistant PdCu alloy cathode material according to claim 8, characterized in that: The atomic ratio of Pd to Cu is greater than 5 and there is a bicontinuous porous structure, the pore size of the bicontinuous porous structure ranges from 4nm to 13nm, and the ligament size of the bicontinuous porous structure ranges from 5nm to 15nm; Preferably, in the methanol-resistant PdCu alloy cathode material, the Pd / Cu atomic ratio is selected from 5 / 1-25 / 1, the pore size range of the bicontinuous porous structure is 5nm-8nm, and the ligament size range is 6nm-8nm.

10. The methanol-resistant PdCu alloy cathode material according to claim 8, characterized in that: The specific surface area of ​​the methanol-resistant PdCu alloy cathode material is in the range of 70 m 2 / g-85m 2 / g; Preferably, the specific surface area ranges from 74m 2 / g-85m 2 / g.

Citation Information

Cited By

  • Nano-porous metal material with hierarchical structure, preparation method of nano-porous metal material and application of nano-porous metal material in electro-catalytic cinnamyl aldehyde hydrogenation

    CN121472627A